ANALISIS EKONOMI USAHATANI SEMANGKA DI KECAMATAN BINAWIDYA KOTA PEKANBARU PROVINSI RIAU - Napitupulu, Candra Tabrani; Ujang Paman (DINAMIKA PERTANIAN, 2024)
The production of watermelons is a lucrative and economically viable business. The objectives of this study are to determine the traits of farmers and the profile of watermelon farming, as well as to examine the costs, yields, revenue, and efficiency of watermelon production in Binawidya District, Pekanbaru City, This study was conducted using the survey method over the course of six months, from April to September of 2023.  A total of 22 farmers were selected as respondents using census method. Descriptive methods, both qualitative and quantitative, were employed for analysis. The study's findings revealed that farmers had an average age of 41, a 9.9-year educational level, 14 years of experience, and a family size of two. An average yield of 15,509 kg/ha/season was produced on 1.57 hectares of land. In each season, 2.429,92 of seeds, 62.03 kg of mulch, 3,777.27 kg of manure, 278.48 kg of dolomite, 49.82 kg of Za, 99.70 kg of NPK, 34.92 kg of KCL, 1.97 liters of bayfolan, 0.86 liters of protectant, 0.96 liters of gandasil, 1.47 kg of anthracol, and 1.07 kg of Dupont were used per hectare. For watermelon farming in Binawidya District, the average production costs each season were IDR 14,386,145/ha, the gross income is IDR 54,282,614/ha, the net income obtained is IDR 39,962,353/ha, and the return cost ratio (RCR) was 3.80. The watermelon farming is economically profitable and efficient business.